Acute Care Surgeons Spend More Time than General Surgeons on the Electronic Health Record (EHR). Issue 5 (May 2023) - Loszko, Abigail; Watson, Michael; Khan, Ahsan; Cunningham, Kyle; Thomas, Bradley; Ross, Samuel; Lauer, Cynthia; Sing, Ronald; Sachdev, Gaurav
Background: The paradigm of Acute Care Surgery (ACS) emerged in response to decreasing operative opportunities for trauma surgeons and increasing need for surgical coverage in disciplines to which the expertise of trauma surgeons naturally extends. While the continued evolution of this specialty remains largely beneficial, unintended consequences may have arisen along the way. One aspect of ACS that remains to be thoroughly investigated is the impact of the electronic health record (EHR). The purpose of this study is to objectively quantify EHR usage for ACS and compare it to other general surgery specialties. Methods: EHR user data were collected for fifteen ACS attendings and thirty-seven general surgery attendings from October 2014 to September 2019. Comparative analysis was conducted using two-tailed t-tests. Subgroup analysis was conducted for subspecialties included in the general surgery group. Results: ACS attendings opened almost 3 times as many charts as general surgery attendings per month (180 vs 64 charts/month, P < .0001), and ultimately spent more time on the EHR as a result (10 vs 6.4 hours/month, P < .0001). Documentation was the most time consuming EHR task for both groups. Although ACS attendings spent less overall time per patient chart, the proportion of time spent on certain EHR tasks was similar to that of general surgery colleagues. Discussion: The EHR imposes a disproportionate burden on ACS attendings compared to their general surgery counterparts, and additional study is warranted to improve usage. EHR usage burden has workforce implications for trainees considering a career in ACS.